(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
Attempts to contain and prevent the spread of 2020’s CoVID-19 pandemic resulted in major supply-chain limitations. Additive manufacturing provided a potential solution through which the manufacturing of critically needed medical equipment could be facilitated. Whilst this led to innovative initiatives with potentially feasible/beneficial outcomes, some solutions did not account for the limitations of the technology. Here a case study is put forward in which a Design for Additive Manufacturing approach is taken for the feasible development of an automated AMBU-bag based ventilator.